Nischarin downregulation attenuates cell injury induced by oxidative stress via Wnt signaling. Issue 17 (9th December 2020) - Guo, Zhanpeng; Huang, Mina; Yuan, Yajiang; Guo, Yue; Song, Changwei; Wang, Hongyu; Dang, Xiaoqian
Abstract : Nischarin (NISCH) is a key protein functioning as a molecular scaffold and thereby hosting interactions with several protein partners. Here, we aimed to investigate whether NISCH downregulation could protect rat pheochromocytoma (PC12) cells against oxidative stress-induced injury using a model of cell injury induced by hydrogen peroxide (H2 O2 ). Cell viability was evaluated using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. Cell apoptosis rate was evaluated using flow cytometry. The expressions of apoptosis-related proteins Bax, Bcl-2, caspase-3 and NISCH were examined via Western blot analysis and immunofluorescence staining analyses. The expressions of NISCH, glycogen synthase kinase-3β (GSK-3β) and T-cell factor-1 (TCF-1) were examined using Western blot analysis. The results showed that incubation of H2 O2 for 48 h significantly decreased the cell viability, increased the cell apoptosis rate and the NISCH expression in PC12 cells, whereas NISCH downregulation blocked the effects of H2 O2 on cells. In addition, the expression of Bcl-2 was significantly reduced, and the expression of Bax and caspase-3 were significantly increased by H2 O2 treatment. However, these effects were partially inhibited by the downregulation of NISCH. Furthermore, H2 O2 significantly weakened the transduction of Wnt signaling, including the increases of GSK-3β and TCF-1 expressions and the decrease of β-catenin expression, while NISCH downregulation attenuated the effect of H2 O2 on Wnt signaling. Moreover, inhibition of the Wnt pathway further decreased the cell viability and promoted the cell apoptosis induced by H2 O2 in PC12 cells. Our results suggest that NISCH downregulation may protect cells against oxidative stress-induced injury through regulating the transduction of Wnt signaling.